Analisis Pengelolaan Obat Di Puskesmas - Eka Anggreny, Dian; Rawalillah, Hamyatri; Suryanti, Dewi; Dora, Agetri (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2024)
Background: Drug management is a series of drug controls starting from the selection process, procurement, distribution, to use. Drug management is closely related to the budget and expenditure of health installations such as hospitals, health centers and pharmacies. Based on the results of an initial survey conducted at the Basuki Rahmat Public Health Center, demand for medicines decreased by 10% with a total of 9,521 patient visits. In 2021, drug receipts increase by 10% with the number of patient visits reaching 21.717 patients. In 2022 there will be an increase in patient visits by 70% with a total of 37.643 patient visits receiving medication, an increase of 30%. This research aims to analyze drug management in Public Health Center. Method: this research uses qualitative methode. Data collecttion used in-depth interview with a total of 5 informants consisting of the Head of Public Health Center, Pharmacist, Pharmacist Assistant and Midwife. Results: The research results showed that the planning process had been made based on drug needs, the process of procuring drugs from the Health Service and procuring drugs using BLUD funds, the process of receiving drugs was according to standards but the quantity was not as requested. Medicine storage uses the FIFO and FEFO systems, the medicine distribution process is according to the request of each department. The management of medication recording and reporting is in accordance with standards but is still done manually. Conclusion: Drug management at the Public Health Center has been implemented well but at the drug procurement stage it is necessary to collaborate with the relevant Health Service to fulfill the medicines proposed by the Public Health Center. Keywords: Medication Management, Public Health Center